Nutrição verus Qualidade de Vida em Oncologia - Paiva, Ivo Cristiano Soares (2016)
Cancer has a stigmatizing nature felt by the sufferer and his familie, associated with the uncertainty of prognosis, causing suffering, and raising issues of the Quality of Life (QOL) of individuals. In order to understand the impact on those having gastrectomy for gastric carcinoma (nutrition versus QOL), its influence on satisfaction with self-care and the nurseÂs role during the health-disease transition process, a Systematic Literature Review (RSL) was conducted, without meta-synthesis and without meta-analysis. The PI[C]OD methodology - Participants; Interventions; [Comparisons]; Outcomes, Study design - was used to develop the research question and to define the criteria for inclusion and exclusion of studies identified, with twelve forming the sample; analysis, interpretation and summary were conducted. From this analysis it can be concluded that nutrition is beneficial when started early, leading to improvement in QOL. The nurse acts as a facilitator in the process, promoting autonomy and independence, to satisfy the needs, expressed or perceived, for self-care. In Portugal, there is a need to recognize the importance of nutrition in minimizing the impact of surgery for gastric carcinoma and to carry out studies in this area to transfer the results into practice.